Investigation of the adsorption of Astrazon Blue FGRL dye in synthetic wastewater using waste mine clay - Özyonar, Fuat; Kobya, Mehmet; Guler, Ulker Asli (My University, 2021)
In this investigation is aimed at the removal of Astrazon Blue FGRL (AB FGRL) (basic dye) from an aqueous solution using waste clay (MC) obtained from the gold mine area. The natural clay was characterized and identified using X-ray diffraction (XRD) analysis.Then, the contact time, adsorbent dosage, pH, initial dye concentration and temperature experiments were carried out in a batch system. The removal efficiency was found to be 97% at pH 7, 80 min, 30oC, 4 g/L MC dosage, 50 mg/L initial dye concentration. The adsorption data are applied to the Langmuir, Freundlich, and Temkin isotherm models. The maximum capacity of waste mine clay (MC) was found to be 191.75 mg/g. The pseudo-second-order kinetic models and Elovich kinetic model were used to examine the adsorption process of Astrazon Blue FGRL. The results of kinetic experiments were defined by the pseudo-second-order model point out a chemisorption reaction. The adsorption thermodynamics were investigated using parameters such as enthalpy change (?Ho), Gibbs free energy change (?Go) as well as entropy change (?So). These calculations reveal that sorption of Astrozon Blue FGRL is endothermic, spontaneous and enthalpy driven. This work provides guidance for using of waste clay materials for applications in the adsorption removal of dye from aqueous solution.
Keywords: Kimya; Analitik; Kimya; Uygulamalı; Çevre Bilimleri; Çevre Mühendisliği; Kimya; İnorganik ve Nükleer